Impact of GAD65 and/or GAD67 deficiency on perinatal development in rats. Issue 2 (31st December 2021) - Jiang, Weiru; Kakizaki, Toshikazu; Fujihara, Kazuyuki; Miyata, Shigeo; Zhang, Yue; Suto, Takashi; Kato, Daiki; Saito, Shigeru; Shibasaki, Koji; Ishizaki, Yasuki; Isoda, Koji; Yokoo, Hideaki; et al.
Abstract: GABA is a major neurotransmitter in the mammalian central nervous system. Glutamate decarboxylase (GAD) synthesizes GABA from glutamate, and two isoforms of GAD, GAD65, and GAD67, are separately encoded by the Gad2 and Gad1 genes, respectively. The phenotypes differ in severity between GAD single isoform‐deficient mice and rats. For example, GAD67 deficiency causes cleft palate and/or omphalocele in mice but not in rats. In this study, to further investigate the functional roles of GAD65 and/or GAD67 and to determine the contribution of these isoforms to GABA synthesis during development, we generated various kinds of GAD isoform(s)‐deficient rats and characterized their phenotypes. The age of death was different among Gad mutant rat genotypes. In particular, all Gad1 −/− ; Gad2 −/− rats died at postnatal day 0 and showed little alveolar space in their lungs, suggesting that the cause of their death was respiratory failure. All Gad1 −/− ; Gad2 −/− rats and 18% of Gad1 −/− ; Gad2 +/− rats showed cleft palate. In contrast, none of the Gad mutant rats including Gad1 −/− ; Gad2 −/− rats, showed omphalocele. These results suggest that both rat GAD65 and GAD67 are involved in palate formation, while neither isoform is critical for abdominal wall formation. The GABA content in Gad1 −/− ; Gad2 −/− rat forebrains and retinas at embryonic day 20 was extremely low, indicating that almost all GABA was synthesized from glutamate by GADs in the perinatal period. The present study shows that Gad mutant rats are a good model for further defining the role of GABA during development.